ПРИНЦИПЫ ПОВЫШЕНИЯ ЭФФЕКТИВНОСТИ МЕЖКУЛЬТУРНОЙ КОММУНИКАЦИИ УЧАЩИХСЯ В ПРОЦЕССЕ ОБУЧЕНИЯ АНГЛИЙСКОМУ ЯЗЫКУ - Менлимуратова, Э.А. (SCIENCE and SOCIETY, 2024)
This article discusses the importance of principles for increasing the effectiveness of intercultural communication of students in the process of teaching English. The principles of teaching reflect the objective laws of the educational process and are aimed at developing the student’s personality. Knowledge of the principles of learning allows you to correctly determine goals, select the content of educational material, choose forms and methods of teaching in accordance with the goal, and organize the educational process according to your own laws.
Keywords: culture; content; educational material; orientation; value; tolerance; connection; activity; language; personality